Economic sanctions in international law and practice - Asada, Masahiko, 1958- (Routledge advances in international relations and global politics., 2020)
"Providing perspectives from a range of experts, including international lawyers, political scientists and practitioners, this book assesses current theory and practice of economic sanctions, discussing current legal and political challenges faced by the international community. It examines both the implementation of sanctions by major powers -the United States, European Union and Japan - as well as assessing the impact of those sanctions through case studies of Russia, Iran, Syria and North Korea. Balancing theoretical analysis of legal considerations with national and regional level empirical analysis, it also includes coverage of sanctions issues by the UN Security Council and the EU, as well as the extraterritorial application of sanctions. A valuable reference for academics and practitioners, Economic Sanctions in International Law and Practice will be useful to those working in the fields of international law, diplomacy, and international political economy"--